Two new species of Prolyda from the Middle Jurassic of China (Hymenoptera, Pamphilioidea) - Wang, Chen (Zookeys, 2016)
Abstract. Two new species of the genus Prolyda Rasnitsyn, 1968, Prolyda dimidia sp. n. and Prolyda elegantula sp. n., are described and illustrated. Both specimens were well-preserved and collected from the latest Middle Jurassic Jiulongshan Formation of Daohugou Village in Inner Mongolia, China. Based on the new morphological data, a key to the five known species of Prolyda is provided. In addition, Prolyda has an enlarged first antennal flagellomere, which means it might have revert to the elongate plesiomorphic state for the antennal configuration as previously documented.